2016
DOI: 10.1080/23279095.2015.1065261
|View full text |Cite
|
Sign up to set email alerts
|

Montreal cognitive assessment (MoCA): Normative data for old and very old Czech adults

Abstract: The principal aim of our study was to present norms for old and very old Czech adults on the Czech version of the Montreal Cognitive Assessment (MoCA) and investigate the influence of social and demographic factors on MoCA performance. We analyzed 540 adults aged ≥ 60 years (5-year age categories; nationally representative sample in terms of sex and educational level), who met strict inclusion criteria for the absence of neurodegenerative disorders and performed within normal range in neuropsychological assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 39 publications
10
75
1
6
Order By: Relevance
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
“…We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31]. Lower level of education was significantly associated with lower scores, correlating with results from other studies [11][12][13][14][15][16][17][18][31][32][33][34][35]. The difference in mean score was 1.4 points between the least and highest educated groups, in agreement with the original suggested method of adding an extra point for low education (≤12 years).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was validation for mild AD dementia with MoCA-CZ scores of 18 ± 5 points which correspond to the estimated MMSE score of 24 points on average [11, 23, 24, 29]. The similar cutoff for AD-MCI in the current study may be explained by the mode of distinction between MCI and dementia patients.…”
Section: Discussionmentioning
confidence: 86%
“…Чувствительность и специфичность MMSE и МоСА в разных возрастных группах вариабельны и зависят от нейропсихологического профиля и уровня образования [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Кроме того, большин-ство шкал адаптировано к амбулаторной оценке и их использование в условиях стационара может быть затруднено.…”
Section: Discussionunclassified